Pengaruh Model Game Based Learning berbantuan Quizwhizzer terhadap Pemecahan Masalah Matematis berdasarkan Self Efficacy - Hafidh, Muhammad Abdullah; Faridah, Luluk; Aini, Khafidhoh Nurul (Postulat : Jurnal Inovasi Pendidikan Matematika, 2025)
Abstract This study aims to determine the effect of the game-based learning model assisted by the QuizWhizzer application on students’ mathematical problem-solving abilities in the topic of linear equations, viewed from different levels of self-efficacy. This research employed a quantitative method with a quasi-experimental design of the non-equivalent control group type. The population consisted of eighth-grade students at SMP Negeri 1 Baureno in the 2024/2025 academic year, with class VIII J as the experimental group and class VIII F as the control group. The research instruments included a self-efficacy questionnaire, tests (pretest and posttest), student worksheets (LKPD), teaching modules, and learning materials. Data analysis was conducted using SPSS 27 through prerequisite tests (normality, homogeneity, and linearity) and hypothesis testing (Independent Samples t-Test). The results showed a significant effect of the game-based learning model assisted by QuizWhizzer compared to conventional learning on students’ mathematical problem-solving abilities, viewed from high (sig. 0.023), moderate (0.048), and low (0.049) self-efficacy levels, all of which were < 0.05. The average posttest scores of students in the experimental class, based on self-efficacy levels, were higher than those in the control class. Therefore, this model is effective as an alternative interactive learning approach to improve students’ mathematical problem-solving skills. Keywords: Game based learning model, Quizwhizzer, Mathematical problem solving, Self efficacy Abstrak Penelitian ini bertujuan guna mengetahui pengaruh model game based learning berbantuan aplikasi quizwhizzer terhadap pemecahan masalah matematis siswa materi persamaan garis lurus ditinjau dari tingkat self efficacy. Penelitian menggunakan metode kuantitatif desain quasi experiment bertipe the non-equivalent control group design. Populasi penelitian meliputi siswa kelas VIII SMP Negeri 1 Baureno tahun pelajaran 2024/2025, dengan sampel terdiri dari kelas VIII J (eksperimen) dan kelas VIII F (kontrol). Penelitian menggunakan instrumen yang meliputi angket self efficacy, tes (pretest dan posttest), LKPD, modul ajar, dan bahan ajar. Analisis data dilakukan menggunakan SPSS 27 melalui uji prasyarat (normalitas, homogenitas, linearitas) dan uji hipotesis (Independent Samples t-Test). Hasil dari penelitian ini membuktikan terdapat pengaruh signifikan model game based learning berbantuan quizwhizzer dibandingkan pembelajaran konvensional terhadap pemecahan masalah matematis siswa ditinjau dari self efficacy tinggi (sig. 0,023), sedang (0,048), dan rendah (0,049), yang semuanya < 0,05. Rata-rata posttest siswa berdasarkan self efficacy kelas eksperimen lebih unggul daripada kelas kontrol. Dengan demikian, model ini efektif digunakan sebagai alternatif pembelajaran interaktif dalam meningkatkan pemecahan masalah matematis siswa. Kata kunci: Model game based learning, Quizwhizzer, Pemecahan masalah matematis, Self efficacy